(untitled) (World Economics and Finance Bulletin, 2024)
The article analyzes the current state of financing of joint stock companies through IPOs and the sale of shares through SPOs. The economic history of Uzbekistan presents the results of 7 public offerings (IPO/SPO) of enterprises Quartz JSC, Kokand Mechanical Plant JSC, Jizzakh Plastics JSC, UzAuto Motors JSC, Uzbekinvest JSC, Uzbektelecom JSC, achievements and problems in this regard. Appropriate conclusions were drawn on the topic and proposals were made.